THE EFFECT OF COMPANY SIZE AND LITIGATION RISK ON ACCOUNTING CONSERVATISM (EMPIRICAL STUDY ON FOOD AND BEVERAGE SUBSECTOR COMPANIES LISTED ON THE IDX - Amelia Aryani; Kasmanto Miharja (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Accounting conservatism is a prudent reaction to financial statements to deal with uncertainty in economic and business activities. The purpose of this study is to test and determine the effect of company size and litigation risk on accounting conservatism. The research population used is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2021-2023. The sampling technique used in this study was the purposive sampling method and obtained 28 companies selected according to the research criteria. This type of research is quantitative using secondary data. The data analysis method used in this study is descriptive statistical analysis, classical assumption test, multiple linear regression and hypothesis testing using SPSS version 27 software. The results obtained partially in this study concluded that company size has a significant effect on accounting conservatism and litigation risk has a significant effect on accounting conservatism. While simultaneously company size and litigation risk have a significant effect on accounting conservatism.